2002
DOI: 10.1159/000064938
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Alcohol Use, and Gallstone Risk in Japanese Men

Abstract: Background/Aim: Results of epidemiological studies concerning the association between smoking and alcohol use and gallstone risk are inconsistent. We examined the relation of smoking and alcohol use to gallstone disease in Japanese men. Methods: We investigated 174 cases having gallstones as determined by ultrasonography, 104 cases of postcholecystectomy state, and 6,906 controls having a normal gallbladder in the consecutive series of 7,637 men aged 48–59 years receiving a retirement health examination at fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…In line with other studies [4,7,8,9,10, 27], alcohol drinking had protective effects on the gallstone risk in men. Also in agreement with other studies [12], coffee drinking increased this risk in men.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with other studies [4,7,8,9,10, 27], alcohol drinking had protective effects on the gallstone risk in men. Also in agreement with other studies [12], coffee drinking increased this risk in men.…”
Section: Discussionsupporting
confidence: 90%
“…Methodological differences may further account for conflicting results with respect to specific factors such as alcohol and coffee. Some studies [4,7,8,9,10] found a protective effect of alcohol consumption on the risk of gallstone, whereas other studies [2, 11] could not confirm this relation. One study [12] found an increased risk of cholelithiasis among coffee drinkers, but other studies [13, 14] observed an inverse relation between coffee consumption and gallstone formation.…”
Section: Introductionmentioning
confidence: 99%
“…The varying results on the relationship between smoking or drinking and cholelithiasis [7,8,9,10,11] may be due to differences in study population, study design, and method of case detection. Although the biological mechanisms of the relationship between smoking and cholelithiasis are unclear [11], increased liver diseases among the smoker group in this study may have caused increased cholelithiasis since some reports show a close relation between cirrhosis and gallstones [37, 38]. Kono et al [11] reported a significant decrease in the prevalence of gallstone and postcholecystectomy status in moderate and heavy drinkers among Japanese men, but the present study showed no association of alcohol with cholelithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The consistent results that cigarette smoking is associated with an increased risk for both gastric and duodenal ulcers [1,2,3,4,5] and chronic liver disease [6] have been obtained in past epidemiological studies. On the other hand, the relationship between cigarette smoking and cholelithiasis was inconsistent [7,8,9,10,11]. Harmful effects of alcohol on chronic liver disease [6, 12] have been shown, but the effects on other diseases were controversial [1, 2,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation